Water temperature and its effect on hydraulic operation of four dripper models - López A., Jesús Enrique; González M., José Jesús; Lizárraga J., Ramón; Díaz V., Tomás; Partida R., Leopoldo; Armenta A., José Oscar (Revista de Ciencias Agrícolas, 2014)
One of the main factors to which field drippers and/or irrigation strips are exposed to is air and water temperature. The state of Sinaloa, located in northwest Mexico, presents a wide range of temperature variation, from 48 °C to 6 °C; consequently, a study was conducted in order to determine the effect of water temperature on the hydraulic operation of four integrated dripper models, as well as the uniformity and variation of discharge performance. We considered four commercial irrigation strip models, with an integrated flat button dripper, in the Culiacan valley area in Sinaloa state, Mexico. The measured flow rate was compared to the calculated flow rate, according to the manufacturers’ hydraulic specifications. Water pressure and temperature were varied. In addition, the uniformity coefficient was obtained using three different models: Christiansen’s coefficient, the Hart and Reynolds coefficient, and the Criddle, Davis, Pair, and Shockley coefficient. All evaluated drippers showed a uniformity coefficient higher than 95%, regardless of the model used, while the variation coefficient was less than 4%.